The Influence of Cigarette Smoking on Dental Implant Survival Rates: A Comparative Analysis of Smokers and Non-Smokers - Hanifa, Rogean (Archive of Orofacial Data Science, 2024)
AIM: The objective of this study is to determine the significant influence of smoking cigarettes on the dental implant survival-failure rate in comparison to the rate in non-smokers. METHODS: An electronic search was conducted for studies published in English, restricted to the period between 2012 and 2022. Pub-Med and Google Scholar were used to search for articles comparing the success vs. failure rates of dental implants between smokers and non-smokers. RESULTS: Smokers have a higher failure rate, with the duration and amount of smoking being significant factors compared to non-smokers. Moreover, osseointegration was adversely affected by smoking, and smoking accelerated marginal bone loss. Patients who quit smoking showed the same success rates as non-smokers. CONCLUSION: Implant insertion is not an absolute contraindication for smokers, but patients should be informed about all risk factors (bone healing issues, osseointegration, and implant failure). They should be aware that consuming cigarettes during the initial healing phase after implant insertion increases the risk of failure. Advising patients to quit smoking is a viable solution that helps accelerate bone healing and increases the rates of osseointegration and implant success.